ENHANCING STUDENTS’ SPEAKING ABILITY THROUGH COLLABORATIVE LEARNING AT AL MAULIDIYAH ORPHANAGE IN JATIASIH BEKASI - Sri Supeni; Ilham Dhony Pribadi (STIBA IEC JAKARTA, 2021)
The aim of this research was to see the improvement of the EFL learners’ speaking ability through the implementation of Storytelling Strategy using pictures. This research was also directed to explore the beneficial of collaborative learning for students of Al Maulidiyah Orphanage in Jatiasih Bekasi. The subject consisted of 15 of EFL learners. A Classroom Action Research in two cycles had been conducted within 2 meetings for every cycle. The meetings were focused on the interactivity and communicative ability among learners. The research result showed that the learners’ fulfillment of the storytelling task improved from 40% or 66.7%. It also showed that the learners’ ability in speaking performance improved. The highest improvement was seen from fluency indicator that is from 26.7% to 46.7%. While for the other two indicators namely pronunciation and vocabulary move upward a little. In conclusion, the implementation of Interactive Storytelling Strategy increased the EFL learners’ fulfillment of the storytelling task and their speaking ability